The imperative of evidence-based health workforce planning and implementation: lessons from nurses and midwives unemployment crisis in Ghana - James Avoka Asamani; Ninon P. Amertil; Hamza Ismaila; Francis Abande Akugri; Juliet Nabyonga-Orem (BMC, 2020)
Abstract Following periods of health workforce crisis characterised by a severe shortage of nurses, midwives and doctors due to low production rates and excessive out-migration, the Government of Ghana through the Ministry of Health (MOH) responded by expanding training and allowing private sector involvement in the training of health workers especially nurses and midwives. This resulted in substantial increases in the production levels of nurses and midwives even above the projections of the MOH. In this paper, we discuss how a strategy that was seemingly well planned suffered a decade of uncorrected implementation lapses resulting in a lingering need-based shortage of nurses and midwives at service delivery points whilst thousands of trained nurses and midwives remained unemployed for up to 4 years and constantly protesting for jobs. In the short term, we argue that the Government of Ghana would need to increase investment to recruit trained and unemployed nurses and midwives whilst a comprehensive health labour market analysis is conducted to provide robust evidence towards the development of a long-term health workforce plan that would guide future production of nurses and midwives. The Government of Ghana may also explore the option of a managed migration programme to export nurses/midwives to countries that are already destinations to individual migration initiatives in a bid to mitigate the potential skill loss associated with long periods of unemployment after training, especially for those who trained from the private institutions.